IMPLEMENTASI MEDIA PEMBELAJARAN ZOOM MEETINGS BAGI PRESTASI HASIL BELAJAR DI SEKOLAH TINGGI TEOLOGI DUTA PANISAL - Mila Ardila; Yusak Noven Susanto (Metanoia, 2022)
This study aims to provide an understanding to students regarding the Implementation of Zoom Meetings Learning Media For Achievemen ofLearning Outcomes at Duta Panisal Theological College. With this media, students feel helped in learning so that they can achieve good learning achievement results. The method used in this thesis is a qualitative research method using a literature study approach, observation, interviews and documentation. On the theoretical basis there is an explanation of what is meant by the implementation of Zoom Meetings learning Media for Achievement of Learning Outcomes at Duta Panisal Theological College, the Importance of Implementation of Zoom Meetings Learning Media for Achievement of Learning Outcomes at Duta Panisal Theological College which researchers use as a basis for developing research instruments. This research was conducted at the Duta Panisal Theological College campus in accordance with the results listed in the title. This research was conducted on all students of Duta Panisal Theological college. The results of this study are to facilitate the achievement of learning Outcomes that are carried out using media, zoom meetings learning media for achievement learning Outcomes cannot be applied properly due to several factors